Treatment and failure of amalgam restoration analyzed according to class of restoration - AO Olaleye; OP Shaba (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Aims: This is a cross sectional; longitudinal retrospective study to find our reasons for placement of amalgam restoration at a Teaching Hospital in Nigeria and the most common classes of amalgam cavity prepared for amalgam restoration. Material & methods: The record of patients also offended the dental centre of hospital in Nigeria was used for this study and all II records were centralized to separate those that attended the Conservation Dental Clinic for placement were recalled for a cross-examination and comparison with the records. Results: Out of the 431 patients recalled, two hundred and seventy seven turned up (64.3%).  Two thousand and ninety four restoration were placed in regular attendees with classes I,II & V Accounting for 60.08%, 36.77% and 3.16% of all restorations placed respectively, primary caries accounted for 74.1% of all restoration placed, fractured restoration 16.1 % defective margins 3.7%; secondary caries 2.8% dislodged restoration 1.2 %;overcharging amalgam restoration 0.4% cervical abrasion 1.3 % and other reasons which include attrition, iatrogenic preparation accounted for 0.3%. The reasons given for failure in the pooled study was seen repeating itself in that order in Class I and II. Discussion: Class I restorations was the most commonly placed restoration followed by class II and class V restoration, the most common cause of failure in this study in all the classes of restoration was fractured amalgam restoration and the percentage is much higher for class II restorations. This may be due to the high masticatory load it is subjected to as a result of the cultural diet effect practiced in this environment, whereas in other studies carried out in the Caucasian region and other developed economies, secondary caries form the major reason for placement of restoration. Clinical significance: Amalgam fillings are the most commonly performed restoration when treating caries but data in the developing countries on amalgam is sparse and dearth. It is of importance to know the longevity, the failure pattern, shortcoming of the restoration and to find out if the dates in developed countries tally with developing world for analysis and comparison. Conclusion: Dietary habit may be a major reason in failure of amalgam restoration and it is important to note that cultural background may be a deciding factor in the types of failure seen. The problem of over diagnosis of carious lesion may also play a part in primary caries especially in the Teaching Hospital/Dental College unlike what is seen in General Dental centres or Hospital, because Dental students and resident doctors in training are involved in the clerking and treatment of patients.